Controlling Relative miRNA level as Target Therapy of the BRCA Mutation and Its Challenges - Xie, Chenxi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In the past few decades, the diagnosis, prevention, and treatment of BRCA1/2-related cancer, especially breast cancer and ovarian cancer, have been a topic of great concern to scientists and the public. People with mutated BRCA genes are more likely to develop breast and ovarian cancer, and such causes of these types of cancer are inherited. Till now, there is no perfect solution for this gene defect. microRNAs (miRNAs), as important gene expression regulation molecules in humans, are considered to have the potential to be a tool for early diagnosis of such gene defects. In this review, the literature on miRNA closely related to BRCA gene regulation is reviewed, and the mechanism of miRNA causing BRCA gene variation is discussed. The online databases used in this research are PubMed, Nature Journals, ScienceDirect, The European Bioinformatics Institute (EBI), and Google Scholar. The search terms are “BRCA gene mutation”, “BRCA gene function”, “PARP inhibitor”, “miRNA for BRCA regulation”, “Target therapy for BRCA gene mutation”, “Drug resistance”, and “Target specificity”. This paper aims to discuss the possibility of reducing the incidence of BRCA gene mutation by controlling the content of relative miRNAs – reducing miRNAs that inhibit BRCA gene expression and increasing miRNAs that promote BRCA gene expression– and how to restore the function of the mutated BRCA gene by this means. The population that develops breast and ovarian cancer has been on the rise for decades, and the age of patients is getting younger. If miRNA can be developed as an early diagnostic tool, it will enhance the power of current cancer screening techniques and provide a more stable basis for early prevention and subsequent treatment.